2007
DOI: 10.1089/hum.2006.138
|View full text |Cite
|
Sign up to set email alerts
|

Transduction of Human Hematopoietic Stem Cells by Lentiviral Vectors Pseudotyped with the RD114-TR Chimeric Envelope Glycoprotein

Abstract: Lentiviral vectors are efficiently pseudotyped with RD114-TR, a chimeric envelope glycoprotein made of the extracellular and transmembrane domains of the feline leukemia virus RD114 and the cytoplasmic tail of the murine leukemia virus amphotropic envelope. RD114-TR-pseudotyped vectors may be concentrated by centrifugation, are resistant to complement inactivation, and are suitable for both ex vivo and in vivo gene therapy applications. We analyzed RD114-TR-pseudotyped, HIV-1-derived lentiviral vectors for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 23 publications
3
20
1
Order By: Relevance
“…RD2-MolPack-Chim3 has been designed to produce LV for targeting HSC since it carries the RD114-TR envelope, which has been previously (Sandrin et al, 2002;Neff et al, 2004;Di Nunzio et al, 2007) and in this study shown to have a preferential tropism for CD34…”
Section: Discussionmentioning
confidence: 95%
“…RD2-MolPack-Chim3 has been designed to produce LV for targeting HSC since it carries the RD114-TR envelope, which has been previously (Sandrin et al, 2002;Neff et al, 2004;Di Nunzio et al, 2007) and in this study shown to have a preferential tropism for CD34…”
Section: Discussionmentioning
confidence: 95%
“…We coexpressed RD114 glycoprotein as an "entry/fusion" glycoprotein because its receptor is present at high levels on hCD34 ϩ cells and because RD114 glycoprotein LVs efficiently transduce HSCs. 18,19 Insertion of a ligand such as SCF in the influenza HA allowed excellent functional presentation on the LV particles, but completely compromised the vector-cell fusion capacity of the HA glycoprotein. Therefore, SCFHA can bind to the c-Kit receptor but does not efficiently fuse with the target cell.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve this, the VSVG glycoprotein was exchanged for another fusion partner, a mutant RD114 glycoprotein of an endogenous feline virus, RD114 ( Figure 1A). RD114 is an attractive candidate for in vivo use because: (1) RD114 glycoprotein is resistant to degradation by human complement 17 ; (2) RD114-pseudotyped LVs efficiently transduce CD34 ϩ HSCs [17][18][19] ; and (3) a RD114 glycoprotein mutant (RDTR) allowing incorporation onto LVs has been engineered. 17 We report here that RDTR/SCFHA-displaying vectors achieve a highly selective transduction of hCD34 ϩ cells in unfractionated total cord blood (CB) and BM.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, numerous studies have demonstrated pseudotyping of LVs with envelopes from other retroviruses such as MLV, [22][23][24] Gibbon Ape Leukemia Virus (GALV), 25,26 Feline Leukemia Virus (RD114), [26][27][28][29] Amphotropic Retrovirus (Ampho), [30][31][32] 10A1 MLV (10A1), 33,34 and Ecotropic retrovirus (Eco). 31,34,35 Retroviruses are generally conserved in their genome and virion structure.…”
Section: Retroviral Envelopesmentioning
confidence: 99%